Wildlife Bio-Geography on Mangrove Communities in Saparua Island, Maluku - Ernywati Badaruddin; Manuel Kaya; Ivonne R G Kaya (Tropical Small Island Agriculture Management, 2021)
On the island of Nusalaut, an orange crested white cockatoo (Cacatua moluccensis) was found. The interviews with several community leaders from the island of Nusalaut, including Raja Negeri Sila, reveal that there have been no Cacatua moluccensis birds in recent years worldwide Nusalaut. it is predicted that the Cacatua moluccensis bird has moved to Saparua island as the closest island. This bird is no longer found because of changes in the forest's structure and composition into agricultural land for cloves (Eugenia aromatica) because it does not need shade trees. The mangrove community along the coast of the island of Saparua for the last few years has experienced various pressures of development dynamics that have disrupted their lives. Therefore, at the same time, they impact the activities of wildlife that use them as habitat. This research was conducted by applying direct and indirect survey methods to determine the types and distribution of the mangrove community's wildlife inhabitants, both permanently and temporally. Seven species of mammals use the mangrove communities in Saparua Bay, Haria Bay and Tuhaha Bay, nine reptile species, and 18 species of birds.